2017
DOI: 10.1063/1.4971790
|View full text |Cite
|
Sign up to set email alerts
|

Comparing van der Waals DFT methods for water on NaCl(001) and MgO(001)

Abstract: In this work, a range of van der Waals type density functionals are applied to the HO/NaCl(001) and HO/MgO(001) interface systems to explore the effect of an explicit dispersion treatment. The functionals we use are the self-consistent vdW functionals vdW-DF, vdW-DF2, optPBE-vdW, optB88-vdW, optB86b-vdW, and vdW-DF-cx, as well as the dispersion-corrected PBE-TS and PBE-D2 methods; they are all compared with the standard PBE functional. For both NaCl(001) and MgO(001), we find that the dispersion-flavoured func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 52 publications
3
28
0
Order By: Relevance
“…We first consider water monomer and dimer adsorption on the various substrates. The stable adsorption structures identified here agree with those observed in previous studies [20][21][22]25,27,[37][38][39][40][41] . Key structural information is provided in Table 1.…”
Section: Structures and Mechanisms Of Water Adsorption And Diffusionsupporting
confidence: 91%
See 2 more Smart Citations
“…We first consider water monomer and dimer adsorption on the various substrates. The stable adsorption structures identified here agree with those observed in previous studies [20][21][22]25,27,[37][38][39][40][41] . Key structural information is provided in Table 1.…”
Section: Structures and Mechanisms Of Water Adsorption And Diffusionsupporting
confidence: 91%
“…We base our diffusion mechanism discussions on the minimum energy pathway with the lowest barrier, and examples of the other translation pathways are shown in Supplementary Note 5. For water monomer diffusion on non-metal surfaces we find that on NaCl and MgO surfaces, monomers diffuse to adjacent top sites of metal ions through a hopping mechanism over the bridge site, as reported in previous studies 15,41,43 ; and on ZnO(1010), water monomers diffuse along the trenches on the surface, similar to what was found on TiO 2 14 .…”
Section: Structures and Mechanisms Of Water Adsorption And Diffusionsupporting
confidence: 86%
See 1 more Smart Citation
“…20,21 Inclusion of van der Waals corrections leads to a significant increase in the surface energies of all terminations considered, as observed in calculations performed for surfaces of other systems like NaCl or MgO. 28 However, the energy differences between different slabs are comparable to the plain PBE values, and the relative order of stability of stoichiometric surfaces is similar to that found in other calculations, with the exception of the {001} and {111} terminations: the van der Waals-corrected calculation places the {111} surface energy slightly below that of the {001} surface, while plain GGA results find the opposite order. Nonetheless, in agreement with Zhao et al, 22 we also find that the {010} surface becomes more stable at a wide range of chemical potentials if one considers a nonstoichiometric slab created by removing two atom layers from the top and bottom of the slab.…”
Section: A Bulk and Surface Modelsmentioning
confidence: 60%
“…Using a range of dispersion-corrected DFT functionals and water coverages, we recently studied water on the archetypical NaCl(001) and MgO(001) surfaces [10], and found that, for both NaCl(001) and MgO(001), the dispersion-flavored functionals stabilize the water-surface interface by 20%-40% compared to the PBE-results. A monolayer water coverage on MgO(001) leads to a mixed overlayer with both intact and dissociated water molecules in an intricate hydrogen-bonded scheme.…”
Section: Water On Surfacesmentioning
confidence: 99%